Evaluation of quinoline photodegradation from g-C3N4/TiO2 heterostructured materials - Oliveira, Jhonatan Douglas Moura de; Gomes Camara, Alan; Arias, Santiago; Pacheco, José Geraldo de Andrade; Barbosa, Celmy Maria Bezerra de Menezes (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
The commercial TiO₂-P25 is widely used in the photocatalytic degradation of recalcitrant organic compounds; however, it has a band-gap energy of 3.2 eV, meaning it is activated to generate unstable radicals only through ultraviolet radiation [1]. C-N based materials have often been used in heterojunctions with TiO₂, as they improve the optical and electronic properties of the photocatalyst [2]. The objective of this study is to evaluate the synthesis of a 10%g-C₃N₄/TiO₂ heterostructured material, obtained from melamine, and to compare it with commercial TiO₂ P25 in the photocatalytic degradation of quinoline. The catalyst was synthesized from 2 g of melamine dissolved in 40 mL of ethanol, followed by homogenization for 15 min. Then, 4.5 g of TiO₂ P25 was added, and the mixture was homogenized for 1 h. The system was heated to 60°C to evaporate the ethanol. Subsequently, thermal treatment was carried out in a muffle furnace at a heating rate of 5°C min-1, reaching 500°Cand maintaining that temperature for 180 min. The photocatalysis tests were conducted in a batch reactor containing 200 mL of quinoline solution, with a concentration of 20 mg L-1 at pH 6.5, and 0.5 g L-1 of catalyst under O₂ bubbling. The system was kept in the dark for 30 min to achieve adsorption equilibrium, followed by 120 min under artificial light simulating sunlight. The polychromatic light source (UV-A and UV-B) used was a 300W OSRAM E27 lamp, with an irradiance of 4.6 mW cm-2. Thematerial was characterized using XRD, TGA, and N₂ adsorption/desorption techniques. X-ray diffractograms confirmed the presence of TiO₂ in the anatase and rutile phases. TGA analysis revealed that the minimum temperature required for calcination to obtain 10%g-C₃N₄/TiO₂ is 500 °C. Between 550 °C and 700 °C, thermal decomposition of g-C₃N₄ may occur, leading to the formation of graphite and the release of N₂ [3]. The addition of g-C₃N₄ resulted in a slight decrease in the surface area ofcommercial TiO₂ P25 (STiO₂ = 52 m2 g-1 to 48 m2 g-1 in 10%g-C₃N₄/TiO₂). Quinoline degradation after 90 min showed an efficiency of 37.2% by photolysis, 94.2% with commercial TiO₂ P25, and 92.4% with the 10%g-C₃N₄/TiO₂ composite, highlighting the high performance of the catalysts compared to simple photolysis. The heterostructured material showedexcellent photocatalytic performance in quinoline degradation.